Selective autophagy as a potential therapeutic target for neurodegenerative disorders. Issue 9 (September 2018) - Scrivo, Aurora; Bourdenx, Mathieu; Pampliega, Olatz; Cuervo, Ana Maria
Summary: Cells rely on surveillance systems such as autophagy to handle protein alterations and organelle damage. Dysfunctional autophagy, an evolutionarily conserved cellular mechanism for degradation of intracellular components in lysosomes, frequently leads to neurodegeneration. The neuroprotective effect of autophagy stems from its ability to eliminate pathogenic forms of proteins such as α-synuclein or tau. However, the same pathogenic proteins often affect different types and steps of the autophagic process. Furthermore, genetic studies have shown that some proteins related to neurodegeneration, such as huntingtin, participate in autophagy as one of their physiological functions. This complex interplay between autophagy and neurodegeneration suggests that targeting autophagy as a whole might have limited applicability in neurodegenerative diseases, and that future efforts should focus instead on targeting specific types and steps of the autophagic process. This change of strategy in the modulation of autophagy might hold promise for future disease-modifying therapies for patients with neurodegenerative disorders.